The Representation of Indigenous Groups in Costa Rican Social Studies Textbooks (1978–2019) - Naranjo Segura, Juan Carlos (2025)
This article analyzes the historical role of Costa Rican indigenous groups as portrayed in Social Studies textbooks used for pedagogical mediation between 1978 and 2019. The study employs a qualitative methodology and discourse analysis of materials from three publishing houses: Ángela Quirós de Vallejos, Faber-Norma, and Santillana. A total of thirty textbooks were reviewed based on three analytical categories: what is stated, related content, and the characteristics assigned to indigenous peoples. The main conclusion reveals that the historical role of indigenous groups is framed as subjects of the past-static in time, homogeneous, respectful of nature, lacking historical evolution, and irrelevant to contemporary national contexts. This representation reinforces their image as the "first Costa Ricans" and the "others" that facilitate the construction of the national "self," ultimately obscuring their presence in Costa Rica's republican period.